PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE PROBING PROMPTING BERBANTU MEDIA FLASH CARD TERHADAP HASIL BELAJARIPS TERPADU - Rita Diartini; Triani Ratnawuri (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The purpose of this research is to know the effect of learning probing prompting assisted flash card media to the learning outcomes of study of IPS integrated second semester class VII MTs Muhammadiyah Metro academic year 2016/2017.The population in this study is the students of class VII MTs Muhammadiyah Metro academic year 2016/2017 which amounted to 48 students. The sample used is class VIIB MTs Muhammadiyah Metro which amounts to 24 students as experiment class, while class VIIA become control class. This study aims to determine whether there is influence of the use of learning with Probing Prompting Helped Flash Card Media to the results of learning IPS integrated with the formula of simple linear regression. From the data analysis of the results of the study using simple linear regression formula with a significant level of 5% obtained tcount = 3.85 while ttable = 1.72 shows t count > ttable, so the hypothesis accepted, that there is a significant influence from the use of probing prompting model assisted flash card media on the learning outcomes of study of IPS integrated second semester class VII MTs Muhammadiyah Metro academic year 2016/2017.Keywords : Flash card, Learning outcomes, Probing prompting